Pengaruh Ukuran Perusahaan, Kebijakan Dividen, Dan Perencanaan Pajak Terhadap Manajemen Laba - Jeradu, Emerensia Frenaldi (Universitas PGRI Yogyakarta, 2021)
The purpose of this study is to investigate whether the size of a company affects profit management, whether dividend policy affects profit management, and whether tax planning affects profit management. The survey picked a sample of manufacturing companies listed on the Indonesia Stock Exchange. The type of data used in this study is secondary data in the form of company financial statements. Between 2016 and 2018, there were 173 registered manufacturing companies. The sampling method used in this study was Objective Sampling, a sampling method determined by researchers based on certain criteria. Based on the researchers' criteria, 15 sample companies were the manufacturing companies. The results of this survey show that (1) company size does not have a significant impact on revenue management, (2) dividend policy has a positive impact on revenue management, and (3) tax planning has a positive impact on revenue management.